(untitled) (Research, Society and Development, 2021)
Aim: Assessing inspiratory muscle strength and lung function in patients with chronic heart failure (CHF) and obstructive sleep apnea (OSA). Methods: Cross-sectional study carried out with 18 CHF participants (12 men) who presented reduced left ventricular ejection fraction (LVEF) (< 51% for men and < 53% for women), and who also had OSA (from light to severe), which was diagnosed through portable polysomnography exam. Inspiratory muscle strength was measured by determining the maximum inspiratory pressure (Ipmax) through manovacuometry; it was compared to values predicted by sex and age. Forced vital capacity (FVC), forced expiratory volume in one second (FEV1) and tiffenau index (FVC/FEV1) were measured in computerized spirometer; they were compared to predicted values. Results: Inspiratory muscle strength of CHF and OSA (109 ± 29 cmH2O) patients was preserved in comparison to values predicted by sex and age (100 ± 13cmH2O; p= 0.22). Both, CVF and VEF1 recorded lower values in comparison to the predicted ones (p= 0.001). Conclusions: CHF and OSA patients presented preserved inspiratory muscle strength and reduced lung function in comparison to reference values.